TRANSFORMASI PEMBELAJARAN MATEMATIKA PASCABENCANA MELALUI RME-ETHNOPEDAGOGI UNTUK PENGUATAN PEMECAHAN MASALAH SISWA - Hayati, Rahmi; Marzuki; Rohantizani; Fuja Rullayali Br; Rahma Alviana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop mathematics learning in post-disaster situations through the implementation of ethnopedagogy-based Realistic Mathematics Education (RME) to improve students’ problem-solving abilities and psychosocial conditions. Post-disaster conditions often affect students’ concentration, learning motivation, and emotional stability, causing the learning process to become less effective. Therefore, a contextual and student-centered learning approach is needed to support both academic achievement and psychosocial recovery. This study employed a mixed methods approach with an embedded quasi-experimental design using a one-group pretest-posttest model. The participants were 28 students of UPTD SD Negeri 3 Percontohan Peusangan, Aceh. Data were collected through tests, observations, questionnaires, and interviews, then analyzed quantitatively and qualitatively. The findings revealed that RME and ethnopedagogy-based learning improved students’ mathematical problem-solving skills. The students’ average score increased from 54.21 to 78.64 with a significance value of 0.000 < 0.05, while the average N-Gain score of 0.53 was categorized as moderate. In addition, students’ psychosocial conditions also improved, particularly in self-confidence, social interaction, and emotional stability. The integration of Acehnese cultural values, such as mutual cooperation and deliberation, created a more active, meaningful, and supportive learning environment in post-disaster mathematics education.